Association between low-grade chronic inflammation with adipocytokines and body fat mass in superobese male children - Aryono Hendarto; Sudigdo Sastroasmoro; Damayanti Rusli Sjarif (Indonesian Pediatric Society, 2019)
Background Obesity causes adipocytokines dysregulation and enhances the pro-inflammatory response. Low-grade chronic inflammation is related to cardiometabolic diseases. Objective To evaluate the status of low-grade chronic inflammation in pre-pubertal, obese boys and its potential correlation to adipocytokines and body fat mass. Methods This cross-sectional study included pre-pubertal, male, superobese children as the subjects. We determined obesity status using the CDC 2000 BMI-for-age chart. Body fat percentage was measured using bioelectric impedance analysis (BIA). Fasting blood specimens were collected to evaluate hsCRP, leptin, adiponectin, and TNF-Î± levels. Results Eighty subjects were recruited into this study, with a mean age of 6.9 years. Ten subjects (12.5%) had low-grade chronic inflammation (hsCRP level â‰¥ 1 mg/L). The levels of hsCRP was not correlated with leptin, adiponectin, and TNF-Î± levels. A weak, but significant correlation was observed between hsCRP level and body fat mass (r= +0.383; P<0.0001). The hsCRP level increased with increasing body fat mass, until it reached its peak at body fat mass of 28 kg. Beyond that point, hsCRP level was stable. Conclusion Low-grade chronic inflammation begins at a young age in obese children. The hsCRP level has a weak correlation with body fat mass, but no correlation with adipocytokine levels. Prevention and treatment of childhood obesity should be prioritized to prevent further cardiovascular and metabolic diseases.